2008
DOI: 10.1016/j.icarus.2008.05.019
|View full text |Cite
|
Sign up to set email alerts
|

PFS/MEX observations of the condensing CO2 south polar cap of Mars

Abstract: The condensing CO 2 south polar cap of Mars and the mechanisms of the CO 2 ice accumulation have been studied through the analysis of spectra acquired by the Planetary Fourier Spectrometer (PFS) during the first two years of ESA's Mars Express (MEX) mission. This dataset spans more than half a martian year, from Ls ∼ 330 • to Ls ∼ 194 • , and includes the southern fall season which is found to be extremely important for the study of the residual south polar cap asymmetry. The cap expands symmetrically and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…The polar night is an environment driven by dynamical processes rather than radiative processes, revealing the subtle differences between the various dynamical cores and their related assumptions. Therefore, although the LMD‐MGCM and LMD Martian Mesoscale Model share similar physical parameterizations, the two models might yield different diagnostics in the polar night, as is the case between the finite difference LMD‐MGCM and the spectral Oxford Mars GCM (L. Montabone, personal communication, 2007) [see also Giuranna et al , 2008]. In addition to the influence of the chosen numerical method to integrate the dynamical equations, the diagnostics derived from the models are sensitive to the dynamical filtering used in the polar regions to overcome the pole singularity problem.…”
Section: Simulationsmentioning
confidence: 99%
“…The polar night is an environment driven by dynamical processes rather than radiative processes, revealing the subtle differences between the various dynamical cores and their related assumptions. Therefore, although the LMD‐MGCM and LMD Martian Mesoscale Model share similar physical parameterizations, the two models might yield different diagnostics in the polar night, as is the case between the finite difference LMD‐MGCM and the spectral Oxford Mars GCM (L. Montabone, personal communication, 2007) [see also Giuranna et al , 2008]. In addition to the influence of the chosen numerical method to integrate the dynamical equations, the diagnostics derived from the models are sensitive to the dynamical filtering used in the polar regions to overcome the pole singularity problem.…”
Section: Simulationsmentioning
confidence: 99%
“…GCM studies show that a topographic forcing by the Hellas basin creates an asymmetry in the mode of deposition. Precipitation events are more frequent for the anti-cryptic sector than for the cryptic sector (Colaprete et al, 2005;Giuranna et al, 2008). This suggests that the texture should be more granular (smaller grain sizes) for the former compared to the latter.…”
Section: Ice Deposition Processmentioning
confidence: 99%
“…Because CO 2 supersaturation can lead to the generation of CO 2 (dry ice) clouds and snowfall, the longitudinal dependence of CO 2 supersaturation observed in the present study provides information about the nature of CO 2 condensation and deposition in the polar regions on Mars. It has been shown that the mechanism of polar ice cap formation has longitudinal dependence at the south pole [ Giuranna et al , ]. Future studies on the effects of snowfall due to CO 2 supersaturation at specific longitudes in the northern polar region will elucidate the role of such CO 2 snowfall in forming the northern seasonal ice cap.…”
Section: Discussionmentioning
confidence: 99%